No need to worry about the end point assessment for nursing associates. Issue 3 (2nd March 2020) - Stonehouse, David
Abstract : This article discusses the end point assessment (EPA) for the nursing associate apprenticeship. The format of the EPA will depend on when the nursing associate commenced their training. Both formats will be presented, together with the two different occupational standards that apply to each. The article will finish by introducing the nursing associate to the role of end point assessor.